A fast procedure for the estimation of the hydrogen storage capacity by cryoadsorption of metal-organic framework materials from their available porous properties. (18th August 2021) - Villajos, Jose A.; Zimathies, Annett; Prinz, Carsten
Abstract: In order to identify the best porous materials for the cryogenic physisorption of hydrogen, high-throughput calculations are performed starting, i.e., from the collected information in crystallographic databases. However, these calculations, like molecular simulations, require specific training and significant computational cost. Herein, a relatively simple procedure is proposed to estimate and compare hydrogen uptakes at 77 K and pressure values from 40 bar starting from the porous properties of MOF materials, without involving simulation tools. This procedure uses definitions for adsorption and considers the adsorbed phase as an incompressible fluid whose pressure-density change is that for the liquid phase at 19 K. For the 7000 structures from the CoRE MOF database, the average error of the predictions is only of 1% from reference values at 100 bar, with an SD of ±8%. This accuracy is lower than that from simulation tools, but involving lower computational cost and training. Graphical abstract: Image 1 Highlights: Estimation of the hydrogen uptake of MOFs at 77 K and any pressure value over 40 bar. The algorithm uses porous properties from any MOF database and adsorption definitions. Alternative to non-trained people in simulation, fast and reasonably accurate. Potentially useful for adsorption of any gas that reaches superficial saturation.